2000
DOI: 10.1177/088572880002300207
|View full text |Cite
|
Sign up to set email alerts
|

Paid Internships and Employment Success for Youth in Transition

Abstract: This article presents information on the characteristics and postschool outcomes of youth who participated in the Marriott Foundation's Bridges... from school to work internship program at seven national sites from 1993 to 1997. A comprehensive database of 3,024 participants was analyzed to determine the extent to which participant and programmatic variables predict post-school employment status at 6, 12, and 18 month follow-up intervals. Neither gender, race, or primary disability made a significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 12 publications
9
78
1
1
Order By: Relevance
“…However, gender, GPA, and the number of credit-hours completed were found to affect none of the five internship impact areas. Our finding of no effect of gender is consistent with the findings of Brush (2013), Luecking and Fabian (2000), Hergert (2009), andGault et al (2000); and is inconsistent with the findings of Ju et al (1998), Raelin et al (2007), Farazmand (2012), andJackel (2011). In addition, our finding of no effect of GPA and credit-hours is consistent with the findings of Hayes (1981), Gault et al (2000), and Casado (1991); and inconsistent with the findings of Hergert (2009Hergert ( , 2011, Gault et al (2000), and Beard and Morton (1999).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…However, gender, GPA, and the number of credit-hours completed were found to affect none of the five internship impact areas. Our finding of no effect of gender is consistent with the findings of Brush (2013), Luecking and Fabian (2000), Hergert (2009), andGault et al (2000); and is inconsistent with the findings of Ju et al (1998), Raelin et al (2007), Farazmand (2012), andJackel (2011). In addition, our finding of no effect of GPA and credit-hours is consistent with the findings of Hayes (1981), Gault et al (2000), and Casado (1991); and inconsistent with the findings of Hergert (2009Hergert ( , 2011, Gault et al (2000), and Beard and Morton (1999).…”
Section: Discussioncontrasting
confidence: 84%
“…In an investigation of the characteristics and post-school outcomes of youth who participated in the Marriott Foundation's Bridges in the USA, Luecking and Fabian (2000) found that gender did not make a significant difference in the employment status of interns six months post the internship. Similarly, Hergert (2009) found that gender had no correlation with the students' perceived value of a business internship.…”
Section: The Influence Of the Individual Characteristicsmentioning
confidence: 99%
“…Overall, more than 80% of students who secured a paid-work experience at school exit remained employed during the first 6-month follow-up period, although rates tended to fall off thereafter (Fabian et al, 1998;Luecking, & Fabian, 2000).…”
Section: Prior Evaluations Of Bridges Program Employment Outcomesmentioning
confidence: 98%
“…The Real Opportunities project has built on research evidence and a model piloted at In response to research that suggested people with intellectual disabilities had poor experience of work environments (Baer et al, 2003;Luecking & Fabian, 2000) Real…”
Section: The Interventionmentioning
confidence: 99%
“…Often, however, staff with expertise in employment who know the labour market are commonly not involved in setting transition goals with young people (Shogren and Plotner, 2012). The abilities of young people can also be a barrier to employment, with poor levels of independence (Carter, Austin and Trainor, 2012;Roessler, Brolin and Johnson, 1990); few experiences of jobs (Baer et al, 2003;Luecking and Fabian, 2000), and poor social skills (Carter, Austin and Trainor, 2012) all making it difficult for them to become employed.…”
mentioning
confidence: 99%